Individual counseling to argue in social media - Erlangga, Erwin (COUNS-EDU: The International Journal of Counseling and Education, 2017)
The purpose of this study is to improve students' argumentation skills in social media. The subjects were 20 students who were divided into two groups: the control group consisting of 10 people and the experimental group consisting of 10 people. The technique used was an quasi experiment with 10 interventions using individualized counseling services to the control group and experimental group. Based on the quasi experimental results by giving counseling to 20 students 10 times and analyzed, students' argumentation skill level increased after individual counseling. Shown with change of skill level of argumentation before treatment (preliminary evaluation) and after (final evaluation) as much as 90 points and through test using test with significance level 5% show t count = 7.077> t table = 2,179. Based on the results of these calculations, show that the hypothesis mentions individual counseling affect students' argumentation skills can be accepted.